Efecto de la Aplicación de las Normas Internacionales de Información Financiera en las Administradoras de Fondos del Distrito Metropolitano de Quito hasta el año 2012 - Guerrero Chavez, Carmen Alexandra (2015)
The economic and political situation in our country in recent years has led us to witness major changes in the financial sector, leading to analyze increasingly more promising and safe to put our resources sector. That's why fund managers have grown incredibly in your business significantly despite the crisis the country has also suffered with the implementation of the new law that gave the Superintendency of Companies to apply International Financial Reporting Standards, fund managers see their clear and useful for managers, investors and good management information. The impact that we see reflected in this research is evident in specific accounts of their accounts, we see an effect of up to 60% on assets and liabilities and deferred in equity can also see that the users of this information handled fully each of the issues because, over time they managed to solve the problems that arose from the outset , plus they agree that the rules are applied IFRSs was a wise decision of the regulator as well as transparent and standardize information , has managed to increase the profits and a worldwide this sector in our country . The Association of Fund Managers also contributed to this change because it ensured the interests of partners and fostering relationships.